Parental intimate partner violence and abuse during the COVID-19 pandemic: Learning from remote and hybrid working to influence future support. (October 2022) - Alderson, Hayley; Barrett, Simon; Addison, Michelle; Burns, Samantha; Cooling, Victoria; Hackett, Simon; Kaner, Eileen; McGovern, William; Smart, Deborah; McGovern, Ruth
Objectives: The COVID-19 pandemic has exacerbated intimate partner violence and abuse. Incidents of intimate partner violence and abuse have increased as a result of household tensions due to enforced coexistence (multiple national lockdowns and working from home practices), economic stress related to loss of income, the disruption of social and protective networks and the decreased access to support services. This study aimed to understand how female survivors of parental intimate partner violence and abuse have experienced the adapted multi-agency response to intimate partner violence and abuse during the pandemic and consider learning from remote and hybrid working to influence future support. Method: This study adopted a qualitative research design, utilizing semi-structured interviews and a focus group. Data collection took place between March and September 2021. In total, 17 female survivors of intimate partner violence and abuse took part in the project; we conducted the semi-structured interviews via telephone (n = 9) and conducted an online focus group (n = 8). Results: Findings identified that services for those experiencing intimate partner violence and abuse need to be innovative, flexible and adaptable and 'reach out' to survivors rather than waiting for survivors to 'reach in' and ask for support. Findings show that the digital space highlights 'missed opportunities' for engagement with both professionals and peers and the potential for digital poverty is a key implication, which risks entrenching existing inequalities. Conclusion: In-depth consideration needs to be given to the design, delivery and evaluation of online interventions and provision of support to improve access and acceptability of services, maximize their effectiveness and to support the safety of survivors.